2020
DOI: 10.1530/rep-20-0108
|View full text |Cite
|
Sign up to set email alerts
|

Scribble promotes alveologenesis in the pregnant mammary gland for milk production

Abstract: Mammary glands are comprised of ducts and terminal lobules that form tree-like structures. Luminal epithelial cells in these lobules undergo differentiation into alveolar cells in pregnancy to support milk production. This study reveals that Scribble (SCRIB), a scaffold protein expressed in progesterone receptor (PGR)-positive cells, plays a critical role in mammary gland alveologenesis in mice. We conditionally deleted Scrib using a Pgr-Cre driver. PGR is heterogeneously expressed throughout the luminal epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Furthermore, PTPN12 is a protein tyrosine phosphatase that contributes to the stable 3D acinar formation of mammary epithelial cells ( Sun et al, 2011 ). PGR promotes alveologenesis in the pregnant mammary gland for milk production ( Aikawa et al, 2020 ). In addition, among the seven genes overlapped between Dengchuan cattle and Holstein cattle, we examined the scanning signal of PTDSS1 and found that the CLR value in Dengchuan cattle (∼638) was much higher than that in Holstein cattle (∼431).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PTPN12 is a protein tyrosine phosphatase that contributes to the stable 3D acinar formation of mammary epithelial cells ( Sun et al, 2011 ). PGR promotes alveologenesis in the pregnant mammary gland for milk production ( Aikawa et al, 2020 ). In addition, among the seven genes overlapped between Dengchuan cattle and Holstein cattle, we examined the scanning signal of PTDSS1 and found that the CLR value in Dengchuan cattle (∼638) was much higher than that in Holstein cattle (∼431).…”
Section: Discussionmentioning
confidence: 99%